The last battle endgame on the Western Front, 1918 - Hart, Peter 1955- (Profile Books Ltd, 2018)
"Too ften, the last nmonths of the Great war are an afterthought; a perfunctory end chapter in histories devoted to the better-known stories of the Somme, Passchendaele or the Battle of Jutland. But as Peter Hart ... shows here, the final eight weeks of the war were crucial: filled with drama and suspense, and shaping both the outcome of the conflict and future of Europe beyond it. By August 1918, it had become clear that the Allies would win. But what was unknown was how this defeat would play out - would the Germans hold on, prolonging the fighting deep into 1919, with the loss of hundreds of thousands more young lives, or could the war be won in 1918? As politicians negotiated over the nature of peace - trying on one side to shift blame and on the other to gain praise - the men in the trenches desperately fought to secure victory, with survival seemingly only days, or hours away."